Is visual outcome compromised when next day review is omitted after phacoemulsification surgery? A randomised control trial. Issue 11 (10th November 2003) - Tinley, C G; Frost, A; Hakin, K N; McDermott, W; Ewings, P
Abstract : Aims: To examine the safety implications of omitting first day clinical review following phacoemulsification cataract surgery. Methods: 362 patients were randomly assigned to "same day discharge" (SDD) or "next day review" (NDR). All patients were reviewed approximately 2 weeks after surgery. Results: Of the 174 patients randomised to NDR, 14 (8.0%) were treated for raised intraocular pressure (25–48 mm Hg) on the first postoperative day. Four received increased topical steroids for uveitis (two) and corneal oedema (two). One patient was treated for a significant wound leak. 12 (6.9%) required additional reviews before 2 week follow up for treatment of the following complications: drop toxicity (six), raised intraocular pressure (five), and corneal abrasion (one). Of the 188 randomised to SDD, six (3.2%) returned to the department before the planned review for reassurance of patients' concerns regarding eye symptoms (three), drop toxicity (one) and follow up of previously raised intraocular pressure (one). There were two cases of iris prolapse in the SDD group. In one case, the complication was anticipated and early review had been arranged. Postoperative acuities of 6/12 or better were achieved in 83% of both SDD and NDR patients (p = 0.96 by χ 2 test). Postoperative quality of life scores at 4 months indicating "no or hardly any concern about vision" (VCM1 questionnaire index <1.0) were achieved in 67% SDD and 72.5% NDR (p = 0.26). Conclusion: The intention to discharge patients on the day of surgery, with planned postoperative review at 2 weeks, was associated with a low frequency of serious ocular complications. Differences in the proportions achieving a good visual outcome between the two groups, based on 2 week visual acuity and 4 month quality of life, were not significant.